1997
DOI: 10.1080/001401397187793
|View full text |Cite
|
Sign up to set email alerts
|

The effect of keyboard keyswitch make force on applied force and finger flexor muscle activity

Abstract: The design of the force-displacement characteristics or 'feel' of keyboard keyswitches has been guided by preference and performance data; there has been very little information on how switch 'feel' alters muscle activity or applied force. This is a laboratory-based repeated measures design experiment to evaluate the effect of computer keyboard keyswitch design on applied finger force and muscle activity during a typing task. Ten experienced typists typed on three keyboards which differed in keyswitch make for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 8 publications
2
41
0
2
Order By: Relevance
“…Button design is known to affect users' peak force, tapping rate, comfort level, and muscle activity [17,19]. The defining parameters of a button's response are travel depth, spring stiffness, and position of activation point.…”
Section: Design Space: Activation Point and Other Parametersmentioning
confidence: 99%
“…Button design is known to affect users' peak force, tapping rate, comfort level, and muscle activity [17,19]. The defining parameters of a button's response are travel depth, spring stiffness, and position of activation point.…”
Section: Design Space: Activation Point and Other Parametersmentioning
confidence: 99%
“…there is ample evidence to suggest (Gerard, Armstrong, Rempel, & Woolley, 2002;Rempel et al, 1997) that the design of modern computer keys serves to constrain, but not control, the force used to respond to stimuli.…”
Section: Stockholm University Stockholm Swedenmentioning
confidence: 99%
“…Past research has shown that there was no significant difference in finger force or EMG activity when typists used a keyboard with a make force of 0.43N and a keyboard with a make force of 0.47N (Rempel et al, 1997). When a keyboard of 1.02N make force was introduced, fingertip force and EMG activity increased significantly (p<0.05) by 40% and 20% respectively.…”
Section: Key Travel and Key Forcementioning
confidence: 93%
“…Finger force data, used in Rempel et al (1997) should be collected to show the actual key strike force applied to the keyboard by the subjects. This would be especially helpful in determining whether a no-force keyboard causes users to decrease key strike force.…”
Section: Limitations Of Present Studymentioning
confidence: 99%